2008
DOI: 10.1002/mop.23555
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the fiber temperature during an arc‐discharge

Abstract: The formation mechanisms and properties of arc‐induced gratings are intrinsically related to the temperature attained by the fiber during arc exposure. In this work, we present further results on the estimation of the fiber temperature based on the use of electrically insulated thermocouples. Computer simulations show that under typical arc discharge conditions, the fiber reaches steady‐state thermal equilibrium in less than half a second, having a peak temperature of about 1350°C. © 2008 Wiley Periodicals, In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Due to the existence of these error sources, it is reasonable to explain the difference between the experimental measured value and the calculated value. However, we observed that our result is essentially consistent with others [12,15,17], all of which are in the range of 100-200 × 10 −3 s (within the range of experimental error). The differences result from the fiber used [12], the type of exposure [17], and other experimental conditions.…”
Section: Theory Of Fiber Heating and Coolingsupporting
confidence: 92%
“…Due to the existence of these error sources, it is reasonable to explain the difference between the experimental measured value and the calculated value. However, we observed that our result is essentially consistent with others [12,15,17], all of which are in the range of 100-200 × 10 −3 s (within the range of experimental error). The differences result from the fiber used [12], the type of exposure [17], and other experimental conditions.…”
Section: Theory Of Fiber Heating and Coolingsupporting
confidence: 92%
“…The theoretical equations governing the intrinsic properties of LPFGs, such as, transmission loss and resonance wavelengths or their temperature and external refractive index dependence, can be found elsewhere [5,[17][18][19][20]. For almost two decades that the underlying mechanisms of arc-induced gratings are under debate and in this context the estimation of the temperature reached by the fiber during an arc discharge allowed a proper discussion on the mechanisms responsible for their formation [21][22][23]. Figure 3 shows that for the typical fabrication parameters used, namely, electric current and time of the arc discharge, the fiber reaches a peak temperature of about 1400 ∘ C in less than half a second (estimated from Figure 3(b)) [23].…”
Section: Mechanisms Of Gratings Formationmentioning
confidence: 99%
“…For almost two decades that the underlying mechanisms of arc-induced gratings are under debate and in this context the estimation of the temperature reached by the fiber during an arc discharge allowed a proper discussion on the mechanisms responsible for their formation [21][22][23]. Figure 3 shows that for the typical fabrication parameters used, namely, electric current and time of the arc discharge, the fiber reaches a peak temperature of about 1400 ∘ C in less than half a second (estimated from Figure 3(b)) [23]. The latter result is also important in order to limit heat diffusion along the fiber since it prevents the use of short grating periods, due to overlap of the effects caused by the adjacent arc discharges.…”
Section: Mechanisms Of Gratings Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that it is possible to obtain significant stress relaxation (corresponding to a Δn~10 −4 ) but an arc current larger than the typical (~9 mA) is needed. Diffusion of fluorine is another possible mechanism; however, for a temperature of 1350°C [8] and arc duration of 0.5 s, the diffusion would account for a refractive index change of only about 5 × 10 −6 [9].…”
Section: Introductionmentioning
confidence: 98%